IMPACT OF PARTICIPATION IN EXTRA CURRICULAR ACTIVITIES ON STUDENTS ACADEMIC SUCCESS IN HEI OF KARACHI (Contemporary Journal of Social Science Review, 2026)
This research investigates the impact of participation in extracurricular activities Students Academic Success in Higher Education Institutions (HEIs) in Karachi. The study aims to fill the existing gap in understanding how students' engagement in extra-curricular influences their academic achievements. The research methodology involves a quantitative with survey method. Population of the study was all students of universities of Karachi, and collecting data through questionnaires distributed online to 60 students from two universities in Karachi South. The study employs a stratified random sampling technique to ensure representation from different institutions. The research instrument, titled "Impact of Participation in Extracurricular Activities on Students Academic Success. "Data was analysis involves Descriptive Statistics, Correlation Analysis, and Regression Analysis using SPSS version 16. The study's significance lies in providing valuable insights for educators, administrators, and policymakers to enhance students' overall development in the context of HEIs in Karachi.